Estimasi Fungsi Konsumsi Pangan dan Non Pangan Penduduk Perkotaan Propinsi Jambi - Bhakti, Adi (Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
This study aims to identify and analyze the development of consumption expenditure of urban residents, the spending patterns of food and non food consumption of urban residents, the MPC for food and non food of urban residents, and the function of food and non food consumption of urban residents in Jambi province. Descriptive analysis method was used as data analysis in this study. The results of this study showed that during the time period of 1993-2011 per capita consumption expenditure of urban residents in Jambi always increase with an average of 52.11 percent per three years, or 17.37 percent annually. Meanwhile, the pattern of consumption expenditure of urban residents Â in Jambi province is still dominated by food consumption expenditure by the average of 55.09 percent while non-food consumption only amounted to 44.01 percent. However, the spending patterns of food and non food consumption of urban residents Jambi province has changed. The function of food consumption of urban residents Jambi province during the period 1993-2011was by 25.8 percent and 23.8 percentÂ for non-food.Keyword: The function of consumption, consumption patterns, food and non-food